Role of Ni dopant on the improvement of ZnO-based reusable photocatalytic materials - Nurfani, Eka; Firdaus, Azka R.; Triyadi, Dedi; Rianjanu, Aditya (Greensusmater, 2024)
This study investigates the impact of Ni doping on the enhancement of ZnO-based reusable photocatalytic materials. Ni concentrations derived from nickel chloride hexahydrate were 0 wt% (ZN-1), 1 wt% (ZN-2), and 3 wt% (ZN-3). Field-emission scanning electron microscopy (FESEM) analysis reveals a significant morphological transformation from flower-like structures in pure ZnO to nanoridges in Ni-doped ZnO. X-ray diffraction data indicate a reduction in crystalline quality with Ni incorporation. UV-Vis spectroscopy shows an increase in the bandgap from 3.22 eV for pure ZnO (ZN-1) to 3.34 eV for Ni-doped ZnO (ZN-2 and ZN-3). Photocatalytic efficiency improves markedly, achieving 30%, 60%, and 80% degradation for ZN-1, ZN-2, and ZN-3, respectively, after 1-hour illumination. Notably, the photocatalytic performance remains robust even after five recycling cycles. These findings reveal the potential of Ni-doped ZnO as a cost-effective, reusable, and highly efficient photocatalytic material.